The Immutability of Taxirutas in Quito, Ecuador: Actions and Strategies from the Informal Transport Sector during Covid-19 - Gamble, Julie (2024)
Between March and May 2020, as cities responded to Covid-19 globally, Quito entered a phase of quarantine that immobilized the city’s public transport system. In this context, this article focuses on how informal transport services continued to operate on the peripheries to provide a mobility service in absence of public transport. The article asks: What did informal transport services such as taxirrutas do during the Covid-19 pandemic? Based on 31 interviews with taxirruta drivers, the article highlights how the sector was characterized by immutability. That is, companies did not change their routes or increase trip prices. The category of immutability, necessarily implies that invisible dynamics like adaptation and maintenance are a requisite for the sector to function without alteration. This article uncovers the strategies and tactics employed to keep a route in motion, which involves heterogeneous dynamics that depend a range of circumstances.